2008
DOI: 10.1097/cad.0b013e3283139100
|View full text |Cite
|
Sign up to set email alerts
|

Agents from amphibians with anticancer properties

Abstract: Amphibians have been found to be a source of agents with anticancer properties. Bufalin, for example, is an anticancer agent that may induce apoptosis by its interaction with other genes and cellular components. Certain peptides with anticancer activities have been found in amphibian skin; they include magainins, aureins, citropin 1.1 and gaegurins. These peptides may exert a cytotoxic effect on human cancer cells through various mechanisms. Onconase, amphinase, cSBL (sialic acid-binding lectin purified from R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 65 publications
2
41
0
Order By: Relevance
“…Bufadienolides, including bufalin, cinobufagin, resibufogenin and telocinobufagin, are the major active constituents derived from Chan Su (32). Chan Su and its constituents have been reported to be able to suppress cellular growth and promote apoptosis in leukaemia, liver, lung and prostate cancers (19). The Chinese medicine preparation, Hua Chan Su, contains bufalin, resibufogenin and cinobufagin, which are derived from Chan Su (33,34).…”
Section: Curcuma Longamentioning
confidence: 99%
See 1 more Smart Citation
“…Bufadienolides, including bufalin, cinobufagin, resibufogenin and telocinobufagin, are the major active constituents derived from Chan Su (32). Chan Su and its constituents have been reported to be able to suppress cellular growth and promote apoptosis in leukaemia, liver, lung and prostate cancers (19). The Chinese medicine preparation, Hua Chan Su, contains bufalin, resibufogenin and cinobufagin, which are derived from Chan Su (33,34).…”
Section: Curcuma Longamentioning
confidence: 99%
“…These include single herbs, traditional herbal formulations and Chinese medicine preparations. A number of single herbs have been individually adopted for cancer treatment, including Radix Astragali (Huang Qi) (16), ginseng (Ren Shen) (17), blister beetle (also known as Mylabris; Ban Mao) (18), toad venom (Chan Su) (19), garlic (Da Suan) (20) and turmeric (Jiang Huang) (21). Chinese traditional herbal formulations were usually developed by ancestors of TCM, and were based on Chinese medicine theories, including yin and yang, the five elements and meridians.…”
Section: Chinese Herbal Medicine In Combined Therapies For Malignanciesmentioning
confidence: 99%
“…Bufadienolides, including resibufogenin, cinobufagin, bufalin, bufotalin and arenobufagin, are a type of steroidal cardiac glycosides (17) that exhibit a variety of biological effects, including cardiotonic, anesthetic and antineoplastic activities (18). Bufalin, as a major active compound of bufadienolide, has been demonstrated to possess significant anti-proliferative activities and apoptosis-inducing effects on human leukaemia, liver, prostatic, endometrial and ovarian cancer cells (19,20). In the present study, we found that another two bufadienolides, resibufogenin and cinobufagin (derived from cinobufacini), inhibit the proliferation of HepG 2 cells in a dose-and time-dependent manner.…”
Section: Effects Of Cinobufagin On the Expression Of Apoptosis-relatementioning
confidence: 99%
“…An aqueous extract from the skin of toad Bufo bufo gargarizans Cantor, which is known as a source of the Chinese traditional medicine cinobufacini (7), has been focused in anticancer studies (8,9). Especially, a series of bufosteroids including bufalin, cinobufagin, and regibufogenin, which are ingredients of the toad skin extract and toad venom, has been found apoptosisinducing ability against cancer cells via cell signaling pathways (8,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%